L' insegnamento della religione ortodossa nella scuola statale greca - Drakulē, Athanasia (Studi e materiali di storia delle religioni, 2009)
In this essay the current situation of the teaching of religion in Greece is presented. The author describes the relationship between the State and the Greek Orthodox Church, the resistance opposed by the religious authorities, and the attempts to democratically change the nature of the religious education that has arisen in Greece over the centuries. The European Community directives challenge Greece to strike a balance between the rights of citizens and the claims of the Church in a pluralist society such as that which is presently coming into being in Europe. (English)